Mapping and quantifying medium-term soil loss rates in mountain olive groves using unmanned aerial vehicle technology - Lima-Cueto, Francisco Javier; Blanco-Sepúlveda, Rafael; Andújar, Dionisio (Elsevier, 2024)
Olive groves are one of the main agroecosystems in the Mediterranean region, but water erosion, aggravated by inappropriate soil management, is compromising the environmental sustainability of these crops. National and international public organisations, including the European Union via its Common Agricultural Policy, have acknowledged the problem and recognise the need to quantify the effects of this process. However, the variability of currently available short-term soil erosion measurements, together with limited understanding of the underlying processes, mean there is considerable uncertainty about the long-term effects of soil erosion. This paper presents an innovative procedure called SERHOLIVE4.0 designed to measure and model long-term soil erosion rates in olive groves, by means of structure-from-motion (SfM) techniques by which im- age information is obtained from unmanned aerial vehicles (UAVs). For the present study, the procedure was evaluated in mountain olive groves, where the erosion rate was calculated from historical surface reconstructions. Overall, this approach was found to be practical and effective. The method includes the following steps: [1] measure the current relief using UAV technology; [2] reconstruct the historical relief from field measurements; [3] calculate soil truncation (h) and obtain a soil erosion rate map; [4] determine the erosive dynamics of the slope and establish the relation between tree truncation, slope and mounds. The method we describe presents the following advantages: • it quantifies soil losses by reference to existing tree mounds; • it is straightforward to apply; • its application enhances the calibration of erosion models
Keywords: Suelos - Erosión; Medio ambiente - Protección; Water erosion; Tillage erosion; Tree mounds; Structure-from-motion (SfM); Soil loss rates